The significant role of scoring from set plays in the 2018 FIFA World Cup - Vergonis, A.; Balasas, D.; Michailidis, Y.; Metaxas, T. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKROUND: The aim of this study was to analyze the set-play goals achieved and VAR influence in the 2018 World Cup as well as to examine their impact on game outcome. METHODS: We analyzed 71 goals that have been scored from a set-play during the 2018 World Cup. We did not include the goals achieved during penalty process. Chi2 analysis was used, and the level of significance was set at P<0.05. RESULTS: Overall, 42% of all goals came from set-plays in 64 matches of this tournament, which is on average 1.1 per match. The team that scored one or more goals via set-plays, won 71.1% of the occasions (Chi2=24.368, P<0.001). Results showed that 22 goals achieved from corner kicks, and the most effective delivery area was the goal center area. Most of the goals (75.0%) from indirect free kick came from the sides, which had significant difference with the central area (Chi2=4.000, P<0.05). All the goals (6) from direct free kick, were scored from the central area out of the 16.5-m box and the distance was <25 m from the goal in all of them. In total, 17 referee decisions changed after VAR reviews and 9 resulted in goals and 89% of them impact the current game outcome. CONCLUSIONS: The findings of this study highlighted the importance of scoring from set plays to game outcome. Coaches should be aware of the above findings in to order to make their teams more effective both in terms of attacking and defending a set-play situation.